Analisis Perhitungan PPh Pasal 21 Terhadap Karyawan Penerima Bonus Dengan Metode SAW Guna Menentukan PPh Terutang - Aura Nisa Azzaroh; Beby Hilda Agustin; Agus Athori (Jurnal Akuntan Publik, 2025)
This research aims to analyze the calculation of PPh Article 21 on bonuses in determining the PPh payable to employees. In determining bonuses, this often causes dissatisfaction among employees because the bonus amounts are unequal. So a method is needed to determine the bonus, the SAW method is the approach used because this approach ranks employees based on their assessment and weighting of criteria with the results in the form of a ranking. The results of this ranking will later determine the employee's bonus. The sampling technique used purposive sampling, and research data was collected through documentation and interviews. The results show that the use of the SAW method provides employee assessments for calculating bonuses in accordance with existing assessments and criteria, and the results are different from before. so that the tax income owed by employees will depend on the amount of bonus received by each employee after using the SAW method and the applicable PPh Article 21 rates.